MODERN REQUIREMENTS TO THE QUALITY MANAGEMENT SYSTEM IN DESIGN MANAGEMENT AT THE ENTERPRISES OF AVIATION COMPLEX - V. Gafiatullin (Вестник университета)
The article touches upon the issues of modern and relevant requirements for the quality management systems at domestic enterprises of the aircraft building complex. Special attention is paid to the study of questions connected with the unique experience of the domestic enterprises in the formation and implementation of a quality management system products and their integration with other businesses. In the course of the study was analyzed foreign experience of quality control aircraft manufacturing corporations and made the conclusion about the necessity of certification of domestic enterprises on international standards of quality management system AS/EN/JISQ 9100. At the end of the article justifies the thesis about the formation of their own information system uniting all vendors of aviation products.